A critique on Avicennas (980 1037 A.D) studies on anatomy of the upper respiratory system and some otorhinolaryngologic concepts (Bangladesh Journal of Medical Science, 2017)
Background: Avicenna (also known as Ibn Sina) was arguably one of the outstanding medical scientists and physicians of the time. He made significant contributions in the development of various medical fields in the golden age of Islamic medicine (9-12th century AD) and in Europe. Ibn Sina contributed immensely to human anatomy, physiology, pathology and management of most disorders of the human body. Of paramount importance was the systemic description of the anatomy of various organs and surgical interventions associated with the problems. Although neither formal dissection nor surgical training was recorded during his time, the anatomic and surgical information presented in the Canon of Medicine is congruent with modern advancement. The current study was undertaken to compare Avicennas anatomy of the ear, nose, oral cavity, throat and larynx to modern anatomical texts.Methods: The current work analysed the anatomy information on the ear, nose, oral cavity, throat and the larynx as presented in volumes one and three of the Canon of Medicine. The information was compared to modern anatomic descriptions.Results: Avicenna described correctly the anatomy and functions of the external and internal ear, nose, oral cavity, parts of the throat and larynx. He described voice production in the larynx and subsequent contributions on the nose, uvula and tongue in shaping the syllables. The functional aspects, disorders and their management associated with the ear and the upper respiratory system were also described.Conclusions: The findings show that Ibn Sinas contributions had a major influence on the development and advancement of medical practise. His anatomic explanations are comparable to modern knowledge on the subject. They also show that the Canon of Medicine is still a valuable book in the study of the history of medicine.Bangladesh Journal of Medical Science Vol.16(2) 2017 p.188-193